2016
DOI: 10.1158/0008-5472.can-15-1199
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Activation of Notch Signaling Inhibits PROX1 Activity to Enhance the Malignant Behavior of Thyroid Cancer Cells

Abstract: Papillary thyroid cancer (PTC) is one of the most common endocrine malignancies associated with significant morbidity and mortality. Although multiple studies have contributed to a better understanding of the genetic alterations underlying this frequently arising disease, the downstream molecular effectors that impact PTC pathogenesis remain to be further defined. Here, we report that the regulator of cell fate specification, PROX1, becomes inactivated in PTC through mRNA downregulation and cytoplasmic misloca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 49 publications
2
37
0
1
Order By: Relevance
“…Recently, a researcher has shown that abnormal expression of NMU is associated with a variety of cancers (33). For SERPINA1, there are currently 6 articles pointing out that SERPINA1 may be a key gene for PTC, consistent with our results (28,(34)(35)(36)(37)(38). Clinical studies have shown that high expression of TIMP1 is positively correlated with a poor prognosis of colon, brain, prostate, breast, lung, and several other cancers (39).…”
Section: Discussionsupporting
confidence: 88%
“…Recently, a researcher has shown that abnormal expression of NMU is associated with a variety of cancers (33). For SERPINA1, there are currently 6 articles pointing out that SERPINA1 may be a key gene for PTC, consistent with our results (28,(34)(35)(36)(37)(38). Clinical studies have shown that high expression of TIMP1 is positively correlated with a poor prognosis of colon, brain, prostate, breast, lung, and several other cancers (39).…”
Section: Discussionsupporting
confidence: 88%
“…SERPINA1 is a serine protease inhibitor with targets including elastase, plasmin, thrombin, trypsin, chymotrypsin and plasminogen activator (79). SERPINA1 is regulated by prospero homeobox 1, which may enhance WNT/β-catenin signaling (79).…”
Section: Serpin Family a Member 1 (Serpina1)mentioning
confidence: 99%
“…SERPINA1 is regulated by prospero homeobox 1, which may enhance WNT/β-catenin signaling (79). In general, SERPINA1 has been implicated to serve a role in the chemoresistance of ovarian cancers (79).…”
Section: Serpin Family a Member 1 (Serpina1)mentioning
confidence: 99%
“…Prospero homeobox protein 1 (Prox1), a tumor suppressor is a frequently downregulated protein in thyroid cancer. Inhibition of Notch signaling in BCPAP cells triggered a simultaneous upregulation of PROX1 . Co‐inhibition of HEY1 and HEY2 resulted in significant upregulation of PROX1 in thyroid cancer (BCPAP and TPC1) cells.…”
Section: Notch Signalingmentioning
confidence: 99%
“…Data indicated that NOTCH pathway was involved in downregulation of PROX1 in thyroid cancers and HEY1 and HEY2 combinatorially downregulated PROX1 (shown in Figure ). Tumor growth was markedly reduced in immunodeficient mice grafted with Prox1 expressing BCPAP‐ cells into the back skin . Therefore it was suggested that Notch signaling negatively regulated Prox1 and inhibition of Notch signaling may prove to be effective to increase the expression of tumor suppressor genes in thyroid cancer.…”
Section: Notch Signalingmentioning
confidence: 99%